PENGARUH MARKETING MIX SYARIAH DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA FASHION MUSLIM JN MODE DI KOTA JAMBI - Aninah Tuzarrah; Elyanti Rosmanidar; Sri Rahma (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
The Muslim fashion industry continues to grow. Currently, there are a large number of clothing entrepreneurs in Jambi City, given the economic prospects that allow companies to consistently achieve stable sales, so that consumers can feel confident in purchasing the products they sell. In this case, the role and application of sharia marketing mix and brand image are crucial because they influence the company's sustainability, especially in increasing sales and also influence consumers in making purchasing decisions. This study aims to determine and analyze the influence of sharia marketing mix and brand image on purchasing decisions for JN Mode Muslim fashion in Jambi City. The research method used is quantitative. A sample of 96 respondents was taken using a purposive sampling technique. This study used the SPSS version 25 calculation tool. The results showed that sharia marketing mix had a significant and positive effect on purchasing decisions, brand image had a significant but negative effect on purchasing decisions. Based on data analysis in this study, these variables are valid and reliable. In testing the classical assumptions of this study, the distribution was normal, and there was no heteroscedasticity or multicollinearity.